Legal analysis of the tv series “13 reasons why” - Abreu Sancho, Vanessa Antuanet (2018)
This article studies the legal problems that arise around the series “13 Reasons Why” among which are the induction to suicide, rape, bullying, among others,these are analyzed not only from a legal perspective but also bioethics. Finally, to determine if these acts constitute a crime and if it is possible to file some kind of criminal action against those who committed them.